Orthogonality Measurent of OFDM Signal - Mahendra Sharma; Santhosh Kumar Singh (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In recent days, Orthogonal Frequency Division Multiplexing is the technique to transmit and receive the signal without any overlapping of the signal. OFDM is also a multiplexing technique as well as modulation technique. It is a multi-carrier transmission technique in which single high data stream is divided into a number of lower rate streams that are transmitted simultaneous over some narrow sub channel. In general, OFDM avoids Inter-Symbol Interference (ISI), Inter-Carrier Interference (ICI) and fault transmissions between source and destination node. To measure the performance of the system by using the parameters like Bit Error rate (BER), Spectrum analysis and signal strength detection. Based on the parameters the best system can be identified.